2021
DOI: 10.1111/and.14361
|View full text |Cite
|
Sign up to set email alerts
|

Fear about adverse effect on fertility is a major cause of COVID‐19 vaccine hesitancy in the United States

Abstract: As of June 2021, three vaccines have been issued Emergency Use Authorization (EUA) by the U.S. Food and Drug Administration (FDA) to combat SARS-CoV-2, with approximately 65% of U.S. adults over the age of 18 having received at least one vaccine dose (Hamel, Lopes, Kearney, et al., 2021). However, vaccine hesitancy rates have remained steady, with 10.2% of Americans stating they probably will not get a vaccine and 8.2% stating they would definitely not get a vaccine (Tram et al., 2021). With the emergence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 8 publications
4
37
0
1
Order By: Relevance
“…Such views were more common among the rich and well educated. 32 There have been similar findings in other countries.…”
Section: Fertilitysupporting
confidence: 78%
“…Such views were more common among the rich and well educated. 32 There have been similar findings in other countries.…”
Section: Fertilitysupporting
confidence: 78%
“…According to the findings of an online survey conducted by Turocy et al ( 2021 ) with fertility patients and those hoping to conceive in the next 6 months ( n = 284), more than half of the total participants were hesitant to accept Covid-19 vaccines due to fears of ‘birth defects, unknown long-term health effects on children and risk of pregnancy loss’ (Turocy et al 2021 ). Another survey study by Diaz et al ( 2021 ) also found that fear of adverse effects on fertility was a major cause of Covid-19 vaccine hesitancy in the United States. In this study, it was found that ‘38% of unvaccinated survey respondents believed that COVID-19 vaccines could negatively impact an individual’s fertility, while approximately one-third remained unsure’ (Diaz et al 2021 : p. 2).…”
Section: Data Results and Analysismentioning
confidence: 99%
“…Another survey study by Diaz et al ( 2021 ) also found that fear of adverse effects on fertility was a major cause of Covid-19 vaccine hesitancy in the United States. In this study, it was found that ‘38% of unvaccinated survey respondents believed that COVID-19 vaccines could negatively impact an individual’s fertility, while approximately one-third remained unsure’ (Diaz et al 2021 : p. 2).…”
Section: Data Results and Analysismentioning
confidence: 99%
“…Contemporaneously, getting three vaccinations, in particular those based on mRNA, has been found to reduce the risk of infection and severe courses of COVID-19 with no safety concerns [33] , [34] . The gap between the study results and current prevalences might be influenced by remaining fear of the vaccines (about effects on fertility [35] , adverse side effects [36] ), uncertainty with changing regulations and frustration in particular concerning political statutes [37] . In general, a survey of 811 healthcare workers before the possibility to get vaccinated showed that people needing more information about COVID-19 and people believing COVID-19 not to be a severe illness had more concerns about this vaccine [38] .…”
Section: Discussionmentioning
confidence: 99%